What Makes a Hospital Excellent? A Qualitative Study on the Organization and Management of Five Leading Public Hospitals in China - Zhao J; Wu X; Chen Y; Li T; Han Y; Liu T; Liu Y (Dove Medical Press, 2023)
Jinhong Zhao, Xue Wu, Yuan Chen, Tao Li, Yunrui Han, Tingfang Liu, Yuanli Liu School of Health Policy and Management, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100730, People's Republic of ChinaCorrespondence: Tingfang Liu; Yuanli Liu, School of health policy and management, Chinese Academy of Medical Sciences & Peking Union Medical College, No. 9, Dongdansantiao Street, Dongcheng District, Beijing, 100730, People's Republic of China, Tel +86 13501008967 ; +86 13522592907, Fax +86 010-65105750, Email liutingfang@pumc.edu.cn; liuyuanli_pumc@163.comPurpose: To summarize the organizational and management experiences and explore the organizational theoretical model of five leading public hospitals in China.Patients and Methods: Purposive sampling was used to select five leading hospitals in different regions of China under the National Health Commission and Provincial Health Commission as study hospitals for the study. From August 2021 to March 2022, 8 leaders and 39 managers from these hospitals were surveyed using semi-structured interviews. The data and information were analyzed in four dimensions using thematic analysis and grounded theory, focused on summarizing the experiences and practices of China's leading hospitals in organizational system, culture, operations and performance management, and employee development. This study complied with the COREQ guidelines for reporting qualitative research.Results: An organizational system model of the characteristics of hospital excellence was developed using four core attributes: organizational system, organizational culture, operations and performance management, and employee development; the model was named the System-Culture-Operation-Performance-Employee (SCOPE) model. Organization and management among leaders and managers in China's leading hospitals are based on the SCOPE process, resulting in employees' well-being, patients' positive outcomes, and organizational excellence. In terms of hospital culture, while adhering to the Hippocratic Oath, the hospital is deeply influenced by traditional Chinese culture, which emphasizes "benevolence" and "love", leading all staff to adhere to "patient-centered care and service." In terms of operations management, a separate operations management department is responsible for hospital operations and performance assessment. As for employee development, the staff's sense of reverence for their profession is emphasized and a reasonable salary system and good practice environment are established to promote staff motivation.Conclusion: The SCOPE model reveals the perspectives of leaders and managers in China's leading hospitals regarding organization and management under a Chinese cultural background. These findings can complement the existing literature on hospital management systems.Keywords: hospital management, excellence, lessons, qualitative study, model